2009
DOI: 10.1021/jf8037659
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Phenolic Compounds Inhibit Homocysteine-Induced Endothelial Cell Adhesion Regardless of Their Different Antioxidant Activity

Abstract: In this study, we examine the effect of extra virgin olive oil phenolic compounds on homocysteine-induced endothelial dysfunction and whether the protective effects are related to their different scavenging activities. Structurally related compounds have been assayed for their ability to reduce homocysteine-induced monocyte adhesion as well as the cell surface expression of intercellular adhesion molecule-1 (ICAM-1) in EA.hy.926 cells. As well-known, among the selected phenolic compounds, hydroxytyrosol, homov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 43 publications
0
34
0
1
Order By: Relevance
“…Data concerning effects of different antioxidant phytochemicals [39][40][41][42][43][44][45][46][47][48][49] and plant extracts [44,[50][51][52][53] in cultured endothelial cells appear frequently in the recent literature. However, there are only few publications about the effect of lycopene and lutein [18].…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning effects of different antioxidant phytochemicals [39][40][41][42][43][44][45][46][47][48][49] and plant extracts [44,[50][51][52][53] in cultured endothelial cells appear frequently in the recent literature. However, there are only few publications about the effect of lycopene and lutein [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies confirmed the anti-inflammatory capacity of HT by reducing VCAM-1, intercellular adhesion protein expressions (0.5 to 75 µM) [22,118,133]. Molecular mechanisms leading to this reduction probably involved the reduction of NF-κB activation (0.5 to 75 µM) [22,23].…”
Section: Associated Complications: Oxidative Stress Inflammationmentioning
confidence: 95%
“…Moreover, it can inhibit superoxide anion burst from macrophages but not from neutrophils where it can only scavenge hydrogen peroxide (1 to 50 µM) [116]. It also protects erythrocytes from hemolysis (50 to 200 µM) [117], endothelial cells from monocytes adhesion (0.5 to 2.5 µM) [118] and hepatocytes (10 to 40 µM) [119], and protects from lipid peroxidation in rat livers (5 to 60 µM) [120] as well as from lipid oxidation (10 µM) [91]. …”
Section: Associated Complications: Oxidative Stress Inflammationmentioning
confidence: 99%
“…The antioxidant effects of olive oil polyphenols are attributed to the inhibition of COX-2 and MMP-9 which are regulated by redox-sensitive signaling pathways and typically promote angiogenesis [260]. Extra virgin olive oil reduced cell surface expression of VCAM-1 and ICAM-1 in an in vitro model of inflammation [261,262]. Oleuropein and hydroxtyrosol reduced monocyte adhesion to the endothelial primarily due to the inhibition of VCAM-1 mRNA and protein expression.…”
Section: Functional Foods Rich In Polyphenolsmentioning
confidence: 99%